(untitled) (Международный научный журнал «Инженер», 2026)
Water is the main resource that ensures the continuation of life. Rapid population growth, industrialization, urbanization and widespread agricultural expansion have led to the production of contaminated wastewater. Millions of people die every year from diseases caused by drinking water contaminated with harmful microorganisms. 80% of child deaths and diseases worldwide are associated with poor water quality. The environment is seriously threatened by these pollutants. Removing harmful substances from wastewater is a major problem. Traditional treatment methods allow only 30-40% purification of contaminated water. In our research work, samples were taken from a depth of 20 cm from the outlet of relatively purified wastewater into an open water body to conduct a chemical analysis of sewage wastewater from three-stage treatment processes at the Termez city wastewater treatment plant of Surkhandarya Water Supply A/J. The samples were tested in the laboratory of the Surkhandarya Regional Department of Ecology, Environmental Protection and Climate Change. The results were analyzed and compared with the state standards for the discharge of wastewater into open water bodies.